2024
DOI: 10.2174/1871527322666230508123558
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia-induced Changes in Genomic Expression Leading to Neurodegeneration

Abstract: General anaesthetics (GA) have been in continuous clinical use for more than 170 years, with millions of young and elderly populations exposed to GA to relieve perioperative discomfort and carry out invasive examinations. Preclinical studies have shown that neonatal rodents with acute and chronic exposure to GA suffer from memory and learning deficits, likely due to an imbalance between excitatory and inhibitory neurotransmitters, which has been linked to neurodevelopmental disorders. However, the mechanisms b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…It was revealed that NEAT1 directly affected the expression of miR‐374c‐5p. When NEAT1 was silenced, miR‐374c‐5p was elevated, autophagy and apoptosis were inhibited, and the ratio of tyrosine hydroxylase (TH+) neurons climbed in MPTP‐induced PD animals 148,149 . Similarly, Li et al.…”
Section: Ncrnas As Regulators Of Autophagy In Pdmentioning
confidence: 95%
See 1 more Smart Citation
“…It was revealed that NEAT1 directly affected the expression of miR‐374c‐5p. When NEAT1 was silenced, miR‐374c‐5p was elevated, autophagy and apoptosis were inhibited, and the ratio of tyrosine hydroxylase (TH+) neurons climbed in MPTP‐induced PD animals 148,149 . Similarly, Li et al.…”
Section: Ncrnas As Regulators Of Autophagy In Pdmentioning
confidence: 95%
“…When NEAT1 was silenced, miR-374c-5p was elevated, autophagy and apoptosis were inhibited, and the ratio of tyrosine hydroxylase (TH+) neurons climbed in MPTP-induced PD animals. 148,149 Similarly, Li et al discovered a beneficial association between the transcription of NEAT1…”
Section: Lncrnasmentioning
confidence: 95%